Synchrophasors Based Wide Area Protection and Phasor Estimation : A Review - Muhammad Qasim, Khan; Musse, Mohamud Ahmed; Ahmed Mohamed, Ahmed Haidar; Norhuzaimin, Julai; Mohammad Kamarul, Hassan (2018)
Phasor Measurement Units (PMUs) are normally used in Wide Area Measurement System (WAMS) for vast applications, such as monitoring the transmission system status over bulky areas including the control and protection. Therefore, this paper reviews the power system protection in relation to the synchronized PMUs and the applications of phasor estimation techniques. Furthermore, the paper elaborates the research works on the applications of PMU for diverse features. The structure and types of PMUs are described utilizing the mathematical modeling of simple Discrete Fourier Transform (DFT) with Recursive and NonRecursive estimation methods. The paper also presents the results of some published studies for two algorithms (Recursive and Non-Recursive). The review has revealed that the NonRecursive algorithm is more accurate and gives robust estimation result.